SOCIAL, ECONOMIC, LEGAL, AND CULTURAL IMPACTS OF LAND ACQUISITION FOR THE CONSTRUCTION OF THE NGAWI- KARTASURA TOLL ROAD SEGMENT - Setiowati, Setiowati; Sudirman, Senthot; Khasanah, Dian Dewi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The construction of the Ngawi - Kartasura Toll Road Segment, part of the 90.1-kilometer Solo - Ngawi Toll Road project, aims to improve connectivity and economic growth in Java, but also brings complex impacts in the land acquisition process. This process raises various social, economic, legal, and cultural challenges that require a holistic and participatory approach, including impact mitigation strategies, transparency, and integration with comprehensive regional development planning. This research aims to analyze the social, economic, legal, and cultural impacts of the land acquisition process for the construction of the Ngawi - Kartasura Toll Road Segment on affected communities, as well as evaluate the effectiveness of land acquisition policies and implementation in mitigating negative impacts and maximizing development benefits for local communities. This research uses normative legal research methods with statutory and conceptual approaches, focusing on the analysis of primary, secondary, and tertiary legal materials through literature study. The data analysis technique uses qualitative analysis methods with deductive reasoning. The results show that the land acquisition process for the construction of the Ngawi - Kartasura Toll Road Segment has multidimensional impacts on affected communities, including social, economic, legal, and cultural aspects. Although there are comprehensive legal foundations and mechanisms for impact mitigation and benefit optimization, the effectiveness of their implementation still varies in the field. Efforts to mitigate negative impacts and maximize benefits have been made, but still face challenges such as inconsistencies in land data, land speculation, and community resistance. To improve effectiveness, a more holistic and participatory approach is needed, including strengthening community participation, improving data accuracy, strengthening local government capacity, and better integration with regional development planning.